Comparative motif discovery combined with comparative transcriptomics yield accurate targetome and enhancer predictions - Naval Sanchez, Marina; Potier, Delphine; Haagen, Lotte; Sanchez, Maximo; Munck, Sebastian; Van de Sande, Bram; Casares, Fernando; Christiaens, Valerie; Aerts, Stein

(untitled) (Genome Research, 2012)
The identification of transcription factor binding sites, enhancers, and transcriptional target genes often rely on the integration of gene expression profiling and computational cis-regulatory sequence analysis. Methods for the prediction of cis-regulatory elements can take advantage of comparative genomics to increase signal-to-noise levels. However, gene expression data are usually derived from only one species. Here we investigate tissue-specific cross-species gene expression profiling by high-throughput sequencing, combined with cross-species motif discovery. First, we compared different methods for expression level quantification and cross-species integration using Tag-Seq data. Using the optimal pipeline we derived a set of genes with conserved expression during retinal determination across D. melanogaster, D. yakuba, and D. virilis. These genes are enriched for binding sites of eye-related transcription factors including the zinc-finger Glass, a master regulator of photoreceptor differentiation. Validation of predicted Glass targets using RNA-Seq in homozygous glass mutant confirms that the majority of our predictions are expressed downstream of Glass. Finally, we tested nine candidate enhancers by in vivo reporter assays and found eight of them to drive GFP in the eye disc, of which seven co-localize with the Glass protein, namely scrt, chp, dpr10, CG6329, retn, Lim3, and dmrt99B. In conclusion, we show for the first time the combined use of cross-species expression profiling with cross-species motif discovery as a method to define a core developmental program and we augment the candidate Glass targetome from a single known target gene, lozenge, to at least 62 conserved transcriptional targets.